Mathematical modelling and optimization of snatch lift technique - Nejadian, S. L.; Rostami, M. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
Mathematical modelling and optimization of snatch technique based on dynamic synthesis is the main purpose of this study. The barbell trajectory was proposed as the main index which has been evaluated experimentally by several researchers who have introduced optimum trajectory according to the percentage of the athletes` success. We employ a five-link model to evaluate its behaviour and to obtain its optimum trajectory by minimizing a specific criterion. We solve motion equations together with an equation which represents the performance criterion by means of Pontryagin Maximum Principle (PMP) formulation simultaneously. The results of this model in comparison with other researchers` experimental observations show an improvement to introduce a good predictive model. This model can help the coaches to improve the performance of weightlifters.